Knowing what research organizations actually do, with whom, where, how and for what purpose: Monitoring research portfolios and collaborations - Ekboir, Javier M.; Blundo Canto, Genowefa M.; Sette, Cristina (Elsevier, 2017)
• The paper presents the first components of a cost-effective system that will be able to monitor changes in research organizations' portfolios and collaborations. • The subsystem that has been developed can describe at particular moments of time what research organizations actually do, with whom, where, how and for what purpose. • Social Network Analysis techniques are used to discover configurations in the structure of a research program and network. • The information generated with the system can be used to monitor and evaluate a research program's organizational learning.